Initial trust formation in B2C e -commerce: The effects of social influence and artifacts of institutional trust and social presence on willingness to provide personal information online - Sinclaire, Jollean K (ProQuest Dissertations & Theses, 2007)
Most empirical research on trust in e-commerce has examined user trust formation in the context of an existing relationship with an online company or a proposed relationship with a widely used or well-known Web site. Much less research has been done to examine initial trust formation with an unknown (i.e., unbranded or unheard-of) online company. This research focuses on three influential components that mediate the relationship between online shoppers and online vendors: trust in the Internet infrastructure, social influence, and Web site features of institutional trust and social presence. The purpose of this study is to investigate trust-building strategies that may influence transactions between individuals and unknown Internet firms. In the first study, a sample of 193 graduate and undergraduate students participated in an instrument development survey. In the second study, 628 graduate and undergraduate students participated in a 3 (trust in the Internet) × 3 (social influence) × 3 (site characteristics) between-subjects experiment in which trust in the Internet was measured, susceptibility to social influence was measured and manipulated, and Web site characteristics were manipulated. Based on age and education, graduate and undergraduate students are representative of current and future Internet shoppers. The results of the study indicate significant direct effects for trust in the Internet infrastructure, susceptibility to the social influence of media, and the presence of influential site characteristics, on user willingness to provide personal information online in the context of initial trust formation. A negative media treatment was found to reduce user willingness to provide personal information online. The presence of symbols of trusted third parties was effective in increasing user willingness to provide three forms of personal information: name, address, and credit card number. Web site social presence features increased user willingness to provide a credit card number. These results provide guidance to managers and designers who work to create Web sites that communicate a credible expression of trustworthiness. Knowledge of effective trust-building strategies guide organizations that use the Internet for selling, marketing, or servicing customers to gain maximum benefits from investments in e-commerce applications.